Influence of Individual and Group Priming on Medical Students - McGeown, Helen Rosemary (My University, 2009)
This study investigated the impact of information on level of prototypicality of the ingroup ‘medical students’, comparing self-esteem effects for those primed as individuals with self-esteem effects for those primed as group members. Indication of prototypicality was given by false feedback on purported individual levels of empathy, an important group norm for medical students. As well as priming type having interactive effects with prototypicality information, it was hypothesized that initial self-esteem of participants would also affect self-esteem and individual ratings of empathy after ‘feedback’ was given. In Phase 1, participants read a paragraph priming them in either of the two conditions before they completed an empathy scale and a self-esteem scale. In Phase 2, individuals received ‘feedback’ on their purported levels of empathy before completing scales identical to those used in Phase 1. Results showed that priming condition has a significant interaction with feedback in relation to prototypicality on self-esteem. Those primed as being members of the group ‘medical students’ had significantly lower self-esteem in comparison to those primed as ‘individuals’ when told they had low empathy. Initial self-esteem had no effect on self-esteem in Phase 2 or on empathy ratings in Phase 2. Results are discussed in relation to uncertainty reduction theory, optimal distinctiveness theory and self-enhancement theory.
Keywords: prime type; self-esteem; prototypicality